Olfactory Dysfunction Associated With Neuro-Behcet Disease - Dogan, Remzi; DOĞAN, REMZI; Ertas, Burak; Ozucer, Berke; Birday, Erkingul; Ozturan, Orhan; Veyseller, Bayram (My University, 2017)
Introduction: Neurologic involvement associated with Behcet disease (BD) is defined as a different entity: Neuro-Behcet disease (NBD). Behcet disease presents with olfactory dysfunction. It is not known whether this is the consequence of mucosal involvement or neurologic involvement.